2004
DOI: 10.1525/maq.2004.18.3.376
|View full text |Cite
|
Sign up to set email alerts
|

Embodied Changes and the Search for Gynecological Cancer Diagnosis

Abstract: The detection and successful treatment of cancers is dependent on timely presentation with abnormal and often subtle symptoms. In this article, we draw on research conducted with Australian immigrant women in 2001-02 who experienced delays in diagnosis of gynecological cancer. Data from in-depth interviews with women with gynecological cancer indicated a common trajectory of an "illness career" whereby the search for diagnosis was often painful and lengthy, either because women normalized the abnormal signs or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…At the same time, heuristics also appeared dominant in communication with and from health professionals, such as Alofa's need to keep reiterating to her GP that “something is wrong,” and to “push them” to take action. Our study echoes others (Fitch et al., ; Granek & Fergus, ; Markovich et al., ) identifying that there were instances where women experienced delays because health professionals did not recognise the importance of the history communicated to them.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…At the same time, heuristics also appeared dominant in communication with and from health professionals, such as Alofa's need to keep reiterating to her GP that “something is wrong,” and to “push them” to take action. Our study echoes others (Fitch et al., ; Granek & Fergus, ; Markovich et al., ) identifying that there were instances where women experienced delays because health professionals did not recognise the importance of the history communicated to them.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, women may delay consulting about potential cancer symptoms because they worry about wasting primary health care practitioners' time, and being labelled as a hypochondriac (Cromme et al, 2016). Healthcare providers can also overlook symptoms of endometrial cancer through misattribution of women's reported symptoms (Markovich, Manderson, & Quinn, 2004). Deferring to clinical expertise may incur misdiagnoses that prolong the time to diagnosis, as women may accept clinicians' reassurances even though they are worried (Molassiotis, Wilson, Brunton, & Chandler, 2010).…”
Section: Communicating With Health Professionalsmentioning
confidence: 99%
“…Nonetheless, when they do so, the only story left to be told is one of implied incompetence, pointing the finger at who (physician, patient, or technician) did not know enough to immediately identify the disease from the symptoms. 2 For example, a study by Markovic, Manderson, and Quinn (2004) examines the narrative histories of 14 women with gynecological cancers. These narratives were used to examine women's 'knowledge of and responses to bodily symptoms' leading to their searches for diagnoses (Markovic et al, 2004, p. 381).…”
mentioning
confidence: 99%
“…Four of the women delayed seeking medical care 'at the onset of symptoms' (p. 381), and Markovic and colleagues suggest that the women did so because they did not perceive the 'symptoms' -also referred to as 'physical signs' -as serious. The two narratives quoted from these women (Markovic et al, 2004) never used the word 'symptom,' yet in the discussion the researchers suggest that the women delayed seeking medical attention because 'the significance of the symptoms of dysfunction were dismissed or normalized' (Markovic et al, 2004, p. 384). Privileging symptoms as objective clinical realities limits studies to assessing whether the patient, the medical personnel, or both were competent at recognizing a medical reality.…”
mentioning
confidence: 99%
“…All interviewees described the drawn-out process of gaining a final diagnosis of narcolepsy (cf. Marcovic, Manderson and Quinn 2004). With help from friends and relatives and from the Internet, the parents suggested a diagnosis of narcolepsy to the doctors, but this was usually rejected as unlikely because narcolepsy is so rare.…”
Section: Methods and Aimsmentioning
confidence: 99%